Kiai's Communication Approach in Developing Religious Culture At the Nurul Qornain Islamic Boarding School Jember - Hariyanto, Hariyanto (Lembaga Penerbitan dan Publikasi Ilmiah Program Pascasarjana IAI Sunan Giri Ponorogo, 2021)
Kiai's leadership strategy in developing a religious culture is an effort to implement the strategic ideas that have been designed in the development of the Islamic boarding school organization so that it is always by its main objectives. In Pondok Pesantren Kiai is the main symbol and the only one who has the prerogative in running an educational institution. However, nowadays pesantren is experiencing rapid development where pesantren not only organize religious activities but also manages various other formal educations. Of course, this has implications for the increasing number of educators and education personnel who ultimately need good and proper management. This development certainly needs to be responded with good communication patterns, in order that all pesantren residents can understand the information messages conveyed by Kiai as the highest leader in the pesantren. Therefore, in the management of the Nurul Qornain Islamic Boarding School, Kiai Yazid Karimullah has approaches to effective communication patterns with his students, so that the availability of channels has implications for receiving students for information.